2023
DOI: 10.3399/bjgp.2023.0193
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians’ moral distress when caring for patients experiencing social inequities: a critical narrative inquiry in primary care

Monica L Molinaro,
Katrina Shen,
Gina Agarwal
et al.

Abstract: BackgroundFamily physicians (GPs) working with patients experiencing social inequities have witnessed patients’ healthcare needs proliferate. Alongside increased workload demands fostered within current remuneration structures, this has generated concerning reports of family physician attrition and possible experiences of moral distress.AimTo explore stories of moral distress shared by family physicians caring for patients experiencing health needs related to social inequities.Design and settingA critical narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Shortage of resources, like appropriate equipment or medications, and personal protection materials is described as a source of distress because it hinders the ability to care properly for patients whilst also protecting oneself. Shortages in human resourcing has an impact on individuals’ workload and therefore is an indirect cause of distress [e.g., 38 , 42 , 45 , 71 , 78 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shortage of resources, like appropriate equipment or medications, and personal protection materials is described as a source of distress because it hinders the ability to care properly for patients whilst also protecting oneself. Shortages in human resourcing has an impact on individuals’ workload and therefore is an indirect cause of distress [e.g., 38 , 42 , 45 , 71 , 78 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study sites were always indicated, North America and Europe, specifically England/UK were represented more than other regions. Studies were conducted across a number of different healthcare systems from the non-universal insurance system of the USA [ 40 42 , 44 , 48 , 57 , 62 , 63 , 69 , 76 , 78 , 85 , 87 ] to universal government-funded health system (single-payer) of Italy [ 43 , 64 , 65 , 67 , 86 ], UK [ 6 , 46 , 51 , 66 , 68 , 72 , 74 , 77 , 81 ], Sweden [ 45 ], Canada [ 47 , 49 , 52 , 54 56 , 61 , 70 , 71 , 73 , 75 , 79 , 82 , 84 ], Norway [ 58 60 ] and Australia [ 50 ], to the universal private health insurance system of Netherlands [ 39 ], and the universal public insurance system (social insurance) of Romania [ 53 ]. Although clear themes emerged that related to different healthcare systems and funding mechanisms for care (e.g., what is available to the individuals in that system based on resources and guidelines), overall, descriptions of events which could cause moral distress showed some consiste...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could erode the practitioner's efforts to deliver trauma informed care, with potential consequences for both patients and clinicians. Such structural constraints in a climate of overwork are powerful sources of moral distress and burnout in studies of nurses, midwives and doctors 20,21,22,23 .…”
Section: Comparison With Existing Literaturementioning
confidence: 99%